Analisis Harga Pokok Produksi CPO (Crude Palm Oil) di Pabrik Kelapa Sawit Ajamu PT Perkebunan Nusantara IV - LUMBANTORUAN, YOEL PABEL; AMBARAWATI, I G. A. A.; ANGGRENI, I G. A. A. LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Analysis Cost of Production of CPO (Crude Palm Oil) at Ajamu Palm Oil Mill  PT Perkebunan Nusantara IV Determination of the cost of production is important for a company, to classify costs appropriately. As happened in Pabrik Kelapa Sawit Ajamu where the company did not calculate the cost of goods and did not know their profit because of the finances regulated by the PT Perkebunan Nusantara IV. The purpose of this study was to determine the amount of cost of production and the amount of profit that occurred at PKS Ajamu PT Perkebunan Nusantara IV during 2020. The research method used was full-costing, namely the method of determining the cost of production that calculates all elements of the cost of raw materials, direct labor costs and overhead costs, both variable and fixed. The results show that the components of production costs consist of raw material costs, labor costs and factory overhead costs in CPO production. The cost of producing CPO using the 2020 method is Rp. 200.993.735.153/year. PKS Ajamu produces CPO in 2020 amounting to 36.386.265 kg, based on total production and total production costs, this study obtained the cost of production of Rp 5.523,89/kg. With a CPO selling price of IDR 8.165/kg, the profit obtained by PKS Ajamu PT Perkebunan Nusantara IV in 2020 is IDR 96.100.118.572/year.